Efficacy of Selected Chemotherapeutic and Medicinal Plants on Fungal Fish Pathogens - Rahman, T; Chowdhury, MBR; Faruk, MAR (Progressive Agriculture, 2013)
Studies were conducted to examine the efficacy of selected chemotherapeutic and medicinal plants against common fungal fish pathogens. Four different doses of available fungicidal agents viz., lime + salt, brilliant green, malachite green and methylene blue were applied to the fresh culture of newly isolated fish pathogenic fungi (Aphanomyces invadans, Saprolegnia sp. and Achlya sp.) under in-vitro condition and minimum inhibitory dose (MID) was determined. Based on in-vitro results, chemotherapeutic were applied to the experimental infection of fish (Barbonymus gonionotus). Salt + lime, brilliant green and malachite green offered better results in reducing the rate of infection followed by medium effective methylene blue. Medicinal plants were selected on the basis of previous studies. Crude extracts were prepared from various parts (leaves and bulb) of neem (Azadirachta indica), turmeric (Curcuma longa) and shoti (C. zedoaria) and four different doses were applied to the fresh culture of above mentioned fungal pathogens under in-vitro condition to determine MID. Treatment trial was performed using the MID of the highly effective plant extracts (viz., tumeric, shoti, neem + tumeric and neem + shoti) on experimental infection of fish. Turmeric and neem + tumeric were found to be the most effective ones. Thus, medicinal plants would be an effective and alternative control measure along with selected chemotherapeutic against fungal diseases of fish. DOI: http://dx.doi.org/10.3329/pa.v19i1.17361 Progress. Agric. 19(1): 105 - 116, 2008